Scopolamine regulates the osteogenic differentiation of human periodontal ligament stem cells through lactylation modification of RUNX2 protein - Ying Wu; Pan Gong (Wiley, 2024)
Abstract Periodontal ligament stem cells (PDLSCs) are important mesenchymal stem cells contributing to regenerating lost periodontal tissues and repairing bone defects. Studies on the molecular mechanism affecting the osteogenic differentiation of PDLSCs are necessary. Scopolamine (SCO) is known as a regulator of neural cell damage. The focus of the current study is on unveiling the role of SCO‐mediated molecular mechanism in the osteogenic differentiation of PDLSCs. Through CCK‐8 assay and LDH detection, we confirmed that SCO enhanced the viability of PDLSCs. Moreover, we determined that SCO induced the PDLSCs osteogenic differentiation, according to data of ALP activity measurement and ARS staining. Mechanistically, we performed western blot and identified that SCO could promote the lactylation of runt‐related transcription factor 2 (RUNX2). We also found through rescue assays that knockdown of RUNX2 could reverse the effect of SCO treatment on the osteogenic differentiation of PDLSCs. Further mechanism investigation revealed that lactylation of RUNX2 at K176 site enhances the protein stability of RUNX2 through deubiquitination. Collectively, our present study unveils that SCO stabilizes RUNX2 to promote the osteogenic differentiation of PDLSCs through the lactylation modification of RUNX2.